1990
DOI: 10.3109/10826089009056225
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Role Perceptions in Chemically Dependent Subjects: Adults Versus Adolescents

Abstract: Contrary to expectations, a study of 81 adolescent drug and/or alcohol addicts produced results quite similar to those found among an adult addicted population (Griffin-Shelley, 1986). On the Bem Sex-Role Inventory (Bem, 1974), these young people rated themselves, in descending order, Undifferentiated (43.2%), Masculine (23.5%), Androgynous (18.5%), and Feminine (14.8%). Despite their exaggerated "macho" and "seductive" attitudes and behaviors, which resemble their adult counterparts, chemically dependent adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The predominance of the undifferentiated genderrole identity in our sample is in accordance with recent findings of US studies based on comparable methods [12,34]. In nonclinical populations, this gender-role type is characterised by high depressiveness, low selfesteem, low adjustment and low life satisfaction [25,39,40].…”
Section: Discussionsupporting
confidence: 91%
“…The predominance of the undifferentiated genderrole identity in our sample is in accordance with recent findings of US studies based on comparable methods [12,34]. In nonclinical populations, this gender-role type is characterised by high depressiveness, low selfesteem, low adjustment and low life satisfaction [25,39,40].…”
Section: Discussionsupporting
confidence: 91%
“…People who abuse alcohol and other drugs tend to have lower self-es teem than those who do not abuse drugs (Cookson, 1994;Griffin-Shelley, Sandler, & Lees, 1990;Macdonald & Czechowicz, 1986;Vega, Zimmer man, Warheit, & Apospori, 1993). At least three explanations of the relationship between self-esteem and substance abuse have been sug gested, all of which are consistent with the sociometer model.…”
Section: Substance Abusementioning
confidence: 94%
“…Thus, low selfesteem may serve as an indication of the activation of these dysfunctional attitudes about oneself (Kassel et al, 2007). Finally, studies have demonstrated links between low self-esteem and substance use (Griffin-Shelley, Sandler, & Lees, 1990;Leary, Schreindorfer, & Haupt, 1995;Vega, Zimmerman, Warheit, Apospori, & Gil, 1993;Wu, Wong, Shek, & Loke, 2014;Zhai et al, 2015). One possible mechanism explaining this relationship is that substances are used to diminish negative affect related to rejection or depression (Kassel et al, 2007), which would be consistent with negative reinforcement models of addiction (e.g., Baker et al, 2004).…”
Section: Early Life Experiences Parental Styles and Attachment Stylesmentioning
confidence: 78%